Identifying the Components and Indicators of the Quality of Working Life of Managers - Asgari, Parvaneh; Fathi Vernosfaderani, Leila; Ahghar, Ghodsi (Iranian Journal of Educational Sociology, 2022)
Purpose: The quality of working life due to the improvement of the quality of human resources has been the focus of most managers and planners. As a result, the present research was conducted with the aim of identifying the components and indicators of the quality of working life of school managers. Methodology: This study in terms of purpose was applied and in terms of implementation method was descriptive from type of qualitative. The research population was experts who were familiar with the research field and the samples of this study according to the principle of theoretical saturation were determined 20 people who were selected by non-probability purposive and snowball sampling methods. The research tool was an in-depth interview with experts, whose content validity was confirmed by 10 experts in the field of educational management, and its reliability was calculated by the method of the coefficient of agreement between two coders of 0.77. Finally, the data obtained from the interviews were analyzed by coding method. Findings: The results of the analysis showed that the quality of working life of school managers had 92 indicators in 5 components including the individual factors, group factors, organizational factors, managerial factors and educational factors. Finally, the pattern of components of quality of working life of school managers was drawn. Conclusion: According to the results of this study, in order to improve the quality of working life of school managers should be provided the ground for the improvement of individual, group, organizational, managerial and educational factors affecting it.